PENINGKATAN KINERJA PERANGKAT DESA MELALUI KEPEMIMPINAN DAN KEMAMPUAN KEPALA DESA BERBASIS TRI KAYA PARISUDHA - Ni Luh Putu Eka Yudi Pratiwi; Ni Made Widnyani (ARTHA SATYA DHARMA, 2021)
This study aims to determine the effect of the leadership and ability of village heads based on tri Kaya parisudha on the performance of village officials in Seririt District. The types of data from this study are quantitative and qualitative data and the data sources in this study are primary data and secondary data. The problem in this study is whether leadership has an effect on the performance of village officials in Seririt District, whether the ability of village heads based on tri Kaya parisudha affects the performance of village officials in Seririt District. The results of this study are that Leadership has a positive and significant effect on Device Performance in Seririt District Village, Tri Kaya Parisudha-Based Ability has a positive and significant effect on Device Performance in Seririt District Village.